Rigged rules and double standards trade, globalisation, and the fight against poverty - Watkins, Kevin; Fowler, Penny ([Oxford] Oxfam, 2002)
A critical and detailed analysis of inequalities of world trade systems.
Executive summary -- Trade and globalisation in the twentieth-first century -- Trade as a force for poverty reduction -- Left behind : poor countries and poor people in the international trading system -- Market access and agricultural trade : the double standards of rich countries -- Trade liberalisation and the poor -- Primary commodities, trading into decline -- Transnational companies : investment, employment, and marketing -- International trade rules as an obstacle to development -- Making trade work for the poor -- List of background research papers -- Acronyms -- Oxfam International addresses.
"Make Trade Fair"--Cover.
Keywords: International trade; Globalization; Equality; Poverty -- International cooperation